Mobiliary Art Objects from the Koksharovski Kholm Sanctuary - Alexander F. Shorin; Anastasia A. Shorina (Археология евразийских степей)
The article deals with mobiliary art objects found in the cultural layers of the complex of archaeological sites " Koksharovskiy Kholm sanctuary – Yuryinskoye settlement", located in the mountain forest zone of the Middle Trans-Urals. The archaeological site contains artifacts from the Neolithic, Chalcolithic, Late Bronze Age, and Middle Ages. But the main part of the collection includes artifacts, made of clay and stone, from the Neolithic, known in the literature as cross-grooved items, spherical and biconical findings, ornithomorphic and zoomorphic artefacts, including plastic on vessels, talc rods of segmented shape with and without impression, a drilled stone mace, a fragment of a polished slate knife, back part of which is designed in the form of an ornithomorphic image, flint and ground arrowheads, clay disks without a hole, etc. Some of these artifacts can be considered as cultic ones, because, it is likely that they were used in the rituals held on the sanctuary, which apparently had the status of an interregional cult center.